Rhopalostroma brevistipitatum sp. nov. from Thailand with an extended generic description for Rhopalostroma - Daranagama, Dinushani Anupama; Liu, Xingzhong; Chamyuang, Sunita; Stadler, Marc; Bahkali, Ali; Hyde, Kevin David (Phytotaxa, 2015)
Rhopalostroma species were collected from Northern Thailand and subjected to morph-molecular analysis. One species possessed small, clavate stromata, with short and stout stipes, asci with an amyloid apical apparatus and ellipsoidal, dark ascospores with germ slits. Morphology and combined phylogenetic analysis of ITS, LSU, β-tubulin and RPB2 sequence data, showed it to be a new Rhopalostroma species introduced herein as R. brevistipitatum. A nodulisporium-like asexual morph was produced in culture. A morphological description and photographs of R. brevistipitatum are provided in this paper, with amendments to the generic description.